PESANTREN; AKAR TRADISI DAN MODERNISASI - Zaki Ghufron (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
Islamic Boarding school is an islamic education institution which has an identical tradition in indonesian muslim societuy. This institution has emerged long before the colonialism era in Indonesia. In its long history since years to pursue the concept of modernism, islamic boarding school, sometimes ,has also been perceived negatively because of transnasionalism ideology which is adopted in recent years. In that case, this paper aimed to describe the existence of islamic boarding school in indonesian social life. By argumenting and comparing some previous studies in this case to gain an accurate result. Moreover, this paper is intended to answer some western perception about islamic boarding school in Indonesia, and finally emphasize the role of islamic boarding school as a government partner and its function in creating democracy. Keyword: Islamic Boarding School, Tradition, Modernization.